A novel microstrip fed triple band patch antenna with TM10, TM02 and TM12 induced modes - Revansiddappa S. Kinagi; Ravi M. Yadahalli; Siddarama R. Patil (Bulletin of Electrical Engineering and Informatics, 2023)
In this study, a patch antenna with three different operating frequencies (2.94 GHz, 4.5 GHz, and 5.7 GHz) is proposed. The dimensions of the antenna are as follows: 23.4 mm by 30.4 mm by 1.6 mm. The triple band characteristic may be achieved by adjusting the width of the quarter wave transformer (QWT), which in turn modifies the impedance matching in such a manner as to excite the TM10, TM02, and TM12 modes. These modes are able to have additional verification provided by the current distribution on the patch. Altering the width of the QWT provides the proposed antenna with the ability to fine-tune its resonant frequencies. At the resonant frequencies, the impedance bandwidths of -10 dB are 69 MHz, 40 MHz, and 110 MHz, respectively. 5.7 GHz has a gain of 1.5 dB, while 4.5 GHz has a gain of 0.7 dB, and 2.94 GHz has a gain of 2 dB. Additionally, this antenna finds its applications in wireless systems in the S and C bands of the frequency spectrum. The antennas are validated using a vector network analyzer (VNA) after being simulated with mentor graphics software three-dimensional electromagnetic modeling (3DEM) and analyzed with it.